2022
DOI: 10.3390/foods11091284
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions of Exopolysaccharides from Lactic Acid Bacteria and Their Potential Benefits for Humans and Farmed Animals

Abstract: Lactic acid bacteria (LAB) synthesize exopolysaccharides (EPS), which are structurally diverse biopolymers with a broad range of technological properties and bioactivities. There is scientific evidence that these polymers have health-promoting properties. Most commercialized probiotic microorganisms for consumption by humans and farmed animals are LAB and some of them are EPS-producers indicating that some of their beneficial properties could be due to these polymers. Probiotic LAB are currently used to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 230 publications
1
41
0
Order By: Relevance
“…EPS consists of homopolysaccharides (HoPS) or heteropolysaccharides (HePS), depending on the main chain composition and mechanisms of synthesis. The most HePS-producing bacteria are Lactobacillus, Lactococcus , Streptococcus and Enterococcus strains frequently isolated from fermented dairy products and the human gastrointestinal tract (GIT), whereas most HoPS are produced by Lactobacillus, Leuconostoc, Pediococcus, Streptococcus , and Weissella strains present in animal GIT, vegetables and fermented beverages ( 75 ). EPS-1 contributes to maintaining the intestinal barrier integrity against the disruption by lipopolysaccharide (LPS) in Caco-2 monolayer mediated by enhancing.…”
Section: Commensal Bacterium-derived Factors Promote Intestinal Epith...mentioning
confidence: 99%
“…EPS consists of homopolysaccharides (HoPS) or heteropolysaccharides (HePS), depending on the main chain composition and mechanisms of synthesis. The most HePS-producing bacteria are Lactobacillus, Lactococcus , Streptococcus and Enterococcus strains frequently isolated from fermented dairy products and the human gastrointestinal tract (GIT), whereas most HoPS are produced by Lactobacillus, Leuconostoc, Pediococcus, Streptococcus , and Weissella strains present in animal GIT, vegetables and fermented beverages ( 75 ). EPS-1 contributes to maintaining the intestinal barrier integrity against the disruption by lipopolysaccharide (LPS) in Caco-2 monolayer mediated by enhancing.…”
Section: Commensal Bacterium-derived Factors Promote Intestinal Epith...mentioning
confidence: 99%
“…To deepen the knowledge about the characteristics of EPS produced by L. paracasei CIDCA strains and understand the relationship between EPS features and their functional properties, the degree of polymerization and the monomer composition of each EPS were studied. EPS produced by LAB present a wide range of molecular weight that varies between 10 4 and 10 6 Da for heteropolysaccharides (HePS) and up to 10 8 for homopolysaccharides (HoPS) (Ryan et al, 2015;Daba et al, 2021;Werning et al, 2022), as it was evidenced for L. paracasei strains reported in the literature (Liu et al, 2013;Wang et al, 2022). When studying the molecular weight of EPS from L. paracasei CIDCA strains, it was observed that these EPS have fractions with different molecular weight that goes from low MW fractions of 1 × 10 4 Da to high MW fractions of 5.10 6 Da.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, surface EPS plays a key role in the interaction of the probiotic bacteria with epithelial cells, triggering the biological effect (Bengoa et al, 2018a;Sabater et al, 2020). In fact, the health-promoting effect attributed to the probiotic bacteria has been ascribed to the presence of these biopolymers in many cases (Ale et al, 2020;Bengoa et al, 2021;Werning et al, 2022). Among the diverse health promoting properties ascribed to EPS produced by LAB it can be mentioned their ability to modulate intestinal microbiota, exert immunomodulatory and/or antitumor effect, or reduce cholesterol level (Laiño et al, 2016;Ale et al, 2020;Medrano et al, 2020;Bengoa et al, 2020a;Oerlemans et al, 2021;Simonelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…EPS produced by food-grade LAB is generally acknowledged as safe and can be used as a living alternative to EPS from plant and animal sources. Nowadays, more attention has been paid to the therapeutic applications of EPS from LAB (4)(5)(6). These studies mainly focused on yogurt starters with a technical interest, such as Lactobacillus delbrueckii, Lactococcus lactis, and Lacticaseibacillus casei (7).…”
Section: Introductionmentioning
confidence: 99%